2018
DOI: 10.5223/pghn.2018.21.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Balloon Dilation for Treatment of Congenital Antral Web

Abstract: Congenital antral webs are a rare but relevant cause of gastric outlet obstruction in infants and children. The condition may lead to feeding refusal, vomiting, and poor growth. Due to the relative rarity of the disease, cases of congenital antral web are frequently misdiagnosed or diagnosed with significant delay as physicians favorably pursue diagnoses of pyloric stenosis and gastric ulcer disease, which are more prevalent. We report a case of an eight-month-old female who presented with persistent non-bilio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Although residual web tissue was observed in a few patients, they remained symptom-free. As of endoscopic treatment, several studies have demonstrated both the strength and limitations ( 2 4 , 10 ). Endoscopic treatment requires suitable instrumentation, technical expertise, and multidisciplinary support ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although residual web tissue was observed in a few patients, they remained symptom-free. As of endoscopic treatment, several studies have demonstrated both the strength and limitations ( 2 4 , 10 ). Endoscopic treatment requires suitable instrumentation, technical expertise, and multidisciplinary support ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antral web is considered a rare cause of gastric outlet obstruction in children ( 1 ). The incidence is unclear, yet ever estimated to be 1–3 in 100,000 live births in the literature ( 2 , 3 ). The pathogenesis includes in-utero vascular accident, failure of recanalization, or an excess of localized endodermal proliferation ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] The endoscopic treatment modality for GAW is either balloon dilation or needle-knife incisions. Balloon dilation has proven to be less invasive and effective,[ 6 ] but did not always provide long-term symptom alleviation. [ 1 ] In recent years, several cases have shown that balloon dilatation combined with needle-knife incisions had low risk of perforation or significant bleeding and hence could also be a sufficient treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the mainstay of treatment in symptomatic patients which include web excision with or without pyloroplasty. Endoscopic dilation is gaining popularity in recent times owing to its less invasive nature and is found to be effective especially in older children (4,5).…”
Section: Gastric Outlet Obstruction Due To Antral Web In a Toddlermentioning
confidence: 99%